(3GdeHgLI aj JTMjP GdCPgGf hJYOjd GdCeRLIs - (3GdCfWGcj, GdHUjQ (B- (3GdWHjH, OGhO Hf YeQ, (B1008 (3g`s
(3ChdgG (B:s
(3SHMGf ef SLOJ dg LHGg GdCLQGe UGZQI(B...(3hHYO, adeG cGf JfGaS GdfahSs
(3BNQgG (B:s
(3gPG eG jJYdb HgPG GdHGH heG jfGSH gPG GdeRGL(B... (3hEfeG GNJQfG ef GdCOhjI eG Sgd hLhOg hCecf JMUjdg (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B333s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B701s
(3cTa GdXfhf(B: (3L(B2(3, U(B1946s
(3GdCYdGe(B: (3L(B2(3, U(B333s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs